Tensile Characteristics of Waste BasedNatural Fibre Composites from RiceHusk and Low Density Polythene Waste - Abesinghe, P.M.I.B.; Narayana, S.N.B.M.W.Y.S.; Somarathna, H.M.C.C. (My University, 2022)
Manufacturing new products with waste material has exposeda tremen-dous contribute to sustainable waste management globally.Recently, natural fibreshave gained attention among researchers, engineers and scientists as an alternativereinforcement for synthetic fibre-reinforced polymer composites due to low cost,fairly good mechanical properties, high specific strength,bio-degradability and eco-friendly characteristics. This project was carried out to investigate the tensile proper-ties of waste based Natural Fibre Composite (NFCs) with the use of Rice Husk (RH)as the reinforcement material and the low-density polythene (LDPE) as the matrix.five types of waste based NFCs were developed by varying the weight fraction offibre to LDPE weight, and weight fractions considered in thisstudy are 10, 20, 30,40 and 50%. Simple techniques were used to manufacture NFCs,such as shreddermachine and hot press machine which do not need high expertise. Uniaxial tensiletest was carried out according to the ASTM D3039, using universal tensile testingmachine with displacement control loading method. Load, displacement and timehistories were obtained and further analyses were undertaken by obtaining Young’smodulus, yield stress, yield strain, ultimate tensile stress, failure strain, resiliencemodulus and toughness modulus for each variation. All typesof NFCs with varyingRH content show behaviour of materials having typical nonlinear elastic–plasticregion. Research findings indicated that addition of 20–40%RH content providebetter overall performance under universal tensile behaviour, by mainly consideringthe behaviour under elastic region and ultimate tensile strength.
Keywords: Natural fibre composites; Rise husk; Low-density polythene; Tensile characteristics; Sustainability; Waste management